Developmental Mutators and Early Onset Cancer - Kentsis, Alex; Frank, Steven A. (Frontiers in Pediatrics, 2020)
A new hypothesis suggests that somatic genome remodeling during normal development can cause mutations that explain many early onset cancers in children and adults.